2018
DOI: 10.1007/s11205-018-1929-9
|View full text |Cite
|
Sign up to set email alerts
|

Does It Matter How You Retire? Old-Age Retirement Routes and Subjective Economic Well-Being

Abstract: the main finding being old-age people's paradoxically high financial satisfaction with relatively low income levels (Hansen, Slagsvold, & Moum, 2008). These studies are mainly crosssectional, which leaves unanswered many of the questions on how changes over time, such as retirement and ageing combined with income change affect financial satisfaction. Retirement has been hypothesized as causing either more or less deprivation than the changes in income would lead one to suspect (Berthoud, Blekesaune, & Hancock,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 49 publications
1
11
0
2
Order By: Relevance
“…To this end, our findings are largely consistent with that in a German study by Bonsang & Klein (2012) who use a FE model to report that retirement has a positive impact on Free time satisfaction, a negative impact on household income satisfaction and an insignificant effect on Life satisfaction. Our FE finding is also in line with FE results of a negative relationship between retirement and income satisfaction in an European study by Palomäki (2019). As noted in section 3, while the FE model helps remove time-invariant individual characteristics, it cannot deal with problems associated with reversed causality and measurement errors.…”
Section: Contemporaneous Effects Of Retirement On Wellbeingsupporting
confidence: 90%
See 1 more Smart Citation
“…To this end, our findings are largely consistent with that in a German study by Bonsang & Klein (2012) who use a FE model to report that retirement has a positive impact on Free time satisfaction, a negative impact on household income satisfaction and an insignificant effect on Life satisfaction. Our FE finding is also in line with FE results of a negative relationship between retirement and income satisfaction in an European study by Palomäki (2019). As noted in section 3, while the FE model helps remove time-invariant individual characteristics, it cannot deal with problems associated with reversed causality and measurement errors.…”
Section: Contemporaneous Effects Of Retirement On Wellbeingsupporting
confidence: 90%
“…These findings are also supported by another German study by Abolhassani & Alessie (2013) who use the same method and data to look at the retirement effect on wellbeing of both males and females. Other studies also use a FE model and data from various European countries to show that retirement is associated with lower levels in income satisfaction (Palomäki 2019) or life satisfaction (Sohier et al 2020). 5 To draw a causal effect of retirement on life satisfaction, three studies in this literature employ an instrumental variable method, using retirement age eligibility as instrument (Horner 2014;Kesavayuth et al 2016;Gorry et al 2018).…”
Section: Previous Related Studiesmentioning
confidence: 99%
“…Perceived income adequacy represents subjective measure of income and has been found to represent a robust indicator of objective economic status, as well as valid measure of one's financial capacity (Grable et al, 2013;Litwin & Sapir, 2009). It is also addressed in the literature as a measure of subjective well-being (Bartolini, Bilancini, & Sarracino, 2013;Chan, Ofstedal, & Hermalin, 2002;Cracolici, Giabona & Cuffaro, 2014;Cracolici, Giambona, & Cuffaro, 2012;Hazelrigg & Hardy, 1997;Litwin, 2009;Palom€ aki, 2017Palom€ aki, , 2019, self-rated economic status (Litwin & Sapir, 2009), subjective income security (Ballantyne & Marshall, 2001) and financial satisfaction (Stoller & Stoller, 2003). Previous studies found perceived income adequacy more meaningful in assessing individual's financial capacity than the actual income.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, self-reported health status exhibits a strong positive relationship with subjective income adequacy. Adults who assess their health more positively were more likely to be satisfied with their income status (Ballantyne & Marshall, 2001;Chan et al, 2002;Cracolici et al, 2012;Gildner et al, 2019;Hazelrigg & Hardy, 1997;Hsieh, 2003;Li et al, 2011;Palom€ aki, 2017Palom€ aki, , 2019Stoller & Stoller, 2003).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Earlier studies have found a clear association between subjective economic difficulties and incomes. 10,11 In Finland, earnings-related disability pension accrues from a person's insured work history, and it also includes the projected pension component that compensates for the loss of income from the time of disability retirement to reaching the old-age retirement age. 12 Thus, disability retirement does not necessarily mean low pension income if one's earnings were high before the disability.…”
Section: Introductionmentioning
confidence: 99%